Wong’s oscillation theorem for second-order delay differential equations - Özbekler, A.; Zafer, A. (Нелінійні коливання, 2016)
Let
H(t) := ∫1/(r(s)z²(s)) (∫z(k)f(k)dk) ds,
where z is a positive solution of
(r(t)x')' + q(t)x = 0, t ≥ a,
satisfying
∫1 / (r(s)z²(s)) ds < ∞.
It is well known that, see [J. S. W. Wong, J. Math. Anal. and Appl. — 1999. — 231. — P. 235 – 240], if
limt→∞ H(t) = − lim t→∞ H(t) = ∞,
then every solution of
(r(t)x') + q(t)x = f(t)
is oscillatory.
In this paper we extend Wong’s result to delay differential equations of the form
(r(t)x' (t))' + q(t)x(τ(t)) = f(t).
It is observed that the oscillation behavior may be altered due to presence of the delay. Extensions to Emden – Fowler type delay differential equations are also discussed. Нехай
H(t) := ∫1/(r(s)z²(s)) (∫z(k)f(k)dk) ds,
де z — додатний розв’язок рiвняння
(r(t)x')' + q(t)x = 0, t ≥ a,
що задовольняє умову
∫1 / (r(s)z²(s)) ds < ∞.
Вiдомо (див. [J. S. W. Wong, J. Math. Anal. and Appl. — 1999. — 231. — P. 235 – 240]), що якщо
limt→∞ H(t) = − lim t→∞ H(t) = ∞,
то кожен розв’язок рiвняння
(r(t)x') + q(t)x = f(t)
є осцилюючим.
У цiй статтi результат Вонга поширено на диференцiальнi рiвняння з запiзненням вигляду
(r(t)x' (t))' + q(t)x(τ(t)) = f(t).
Встановлено, що осциляцiйна поведiнка може змiнюватись за рахунок запiзнення. Також розглянуто узагальнення рiвнянь типу Емдена – Фаулера.